Spatially resolved spectroscopy across stellar surfaces: II. high-resolution spectra across HD209458 (G0V) - Dravins, Dainis; Ludwig, Hans-Günter (Arxiv, 2017)
CONTEXT: High-resolution spectroscopy across spatially resolved stellar surfaces aims at obtaining spectral-line profiles that are free from rotational broadening; the gradual changes of these profiles from disk center toward the stellar limb reveal properties of atmospheric fine structure, which are possible to model with 3-D hydrodynamics. AIMS: Previous such studies have only been carried out for the Sun but are now extended to other stars. In this work, profiles of photospheric spectral lines are retrieved across the disk of the planet-hosting star HD209458 (G0V). METHODS: During exoplanet transit, stellar surface portions successively become hidden and differential spectroscopy provides spectra of small surface segments temporarily hidden behind the planet. The method was elaborated in Paper I, with observable signatures quantitatively predicted from hydrodynamic simulations. RESULTS: From observations of HD209458 with spectral resolution R=80,000, photospheric FeI line profiles are obtained at several center-to-limb positions, reaching adequately high S/N after averaging over numerous similar lines CONCLUSIONS: Retrieved line profiles are compared to synthetic line profiles. Hydrodynamic 3-D models predict, and current observations confirm, that photospheric absorption lines become broader and shallower toward the stellar limb, reflecting that horizontal velocities in stellar granulation are greater than vertical velocities. Additional types of 3-D signatures will become observable with the highest resolution spectrometers at large telescopes.